1998
DOI: 10.1128/mcb.18.4.1919
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis Delta Virus RNA Editing Is Highly Specific for the Amber/W Site and Is Suppressed by Hepatitis Delta Antigen

Abstract: RNA editing at adenosine 1012 (amber/W site) in the antigenomic RNA of hepatitis delta virus (HDV) allows two essential forms of the viral protein, hepatitis delta antigen (HDAg), to be synthesized from a single open reading frame. Editing at the amber/W site is thought to be catalyzed by one of the cellular enzymes known as adenosine deaminases that act on RNA (ADARs). In vitro, the enzymes ADAR1 and ADAR2 deaminate adenosines within many different sequences of base-paired RNA. Since promiscuous deamination c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
2
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(135 citation statements)
references
References 39 publications
5
126
2
2
Order By: Relevance
“…As yet, the factors that determine these variations are not well understood. For HDV genotype I (HDV-1), editing is down-modulated in part by HDAg-S (Polson et al 1998;Sato et al 2004), most likely by binding to the RNA. However, we previously observed that HDAg-S is not an effective inhibitor of amber/W site editing for HDV-3, which differs from HDV-1 by z40% in nucleic acid sequence (Cheng et al 2003), thus indicating that an alternative mechanism must exist for the regulation of editing for this genotype.…”
Section: Introductionmentioning
confidence: 99%
“…As yet, the factors that determine these variations are not well understood. For HDV genotype I (HDV-1), editing is down-modulated in part by HDAg-S (Polson et al 1998;Sato et al 2004), most likely by binding to the RNA. However, we previously observed that HDAg-S is not an effective inhibitor of amber/W site editing for HDV-3, which differs from HDV-1 by z40% in nucleic acid sequence (Cheng et al 2003), thus indicating that an alternative mechanism must exist for the regulation of editing for this genotype.…”
Section: Introductionmentioning
confidence: 99%
“…The 0.8-kb mRNA is translated into S-HDAg, which is required for continuous HDV RNA replication (21). In the later stages of viral replication, an RNA editing event occurs at the amber termination codon of the S-HDAg ORF to allow the synthesis of L-HDAg (40,41), which is required for virus assembly (2,24). L-HDAg was also thought to inhibit HDV RNA replication when expressed artificially early in viral replication (4,24), but a recent study showed that L-HDAg does not play a significant role in regulating viral RNA levels in cells (29).…”
mentioning
confidence: 99%
“…Les conséquences de ce processus sur le cycle viral pourraient être très importantes. En effet, l'Ag-S/p24 codé par l'ARNm non édité participe au déclenchement de la réplica-tion virale, tandis que l'Ag-L/p27 produit après l'édition par ADAR inhibe la réplication, ce qui suggère que l'efficacité du processus d'édition jouerait un rôle décisif au cours de l'infection virale [41]. que la modification C-U paraît procéder par un mécanis-me analogue à celui touchant l'ARNm ApoB.…”
Section: Les Paramyxovirus Et Le Virus Ebola : Le Bégaiement De La Réunclassified